2022
DOI: 10.17582/journal.sja/2022/38.3.1140.1146
|View full text |Cite
|
Sign up to set email alerts
|

Response of Maize Growth to Phosphorus, Foliar Zinc and its Application Stage

Abstract: B alanced fertilizer is an essential component that plays a significant role in improving the crop production and quality (Amjadian et al., 2021). Balanced fertilizer also play an important role plant development and yield formation, the presence of essential nutrients in balanced form is necessary (Hi-Abstract | Phosphorus (P), Zinc (Zn) and its application timing play a very important role in crop productivity. To study its effect on maize, an experiment was conducted at Fodder and Forage Crops Section Haric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These results are similar to the results mentioned by [14,23] also they reported that thesis and grain filling stage which in turn may result in increased grain yield. This increased grain yield is the direct result of improvement in yield component, grain size and number of grains per spike had positive correlation with grain yield so highest grain yield might be the direct effect of improvement in grain size and number of grains per spike and many reports indicate the positive correlation of foliar spray of micronutrients with grain yield in wheat [1].…”
Section: Fig3 Grain Yield Relative To the Foliar Application Treatmen...supporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to the results mentioned by [14,23] also they reported that thesis and grain filling stage which in turn may result in increased grain yield. This increased grain yield is the direct result of improvement in yield component, grain size and number of grains per spike had positive correlation with grain yield so highest grain yield might be the direct effect of improvement in grain size and number of grains per spike and many reports indicate the positive correlation of foliar spray of micronutrients with grain yield in wheat [1].…”
Section: Fig3 Grain Yield Relative To the Foliar Application Treatmen...supporting
confidence: 92%
“…The weight of dry matter is significantly affected (p ≤ 0.05) by the foliar feeding of micronutrients (Table 2.). The foliar application of micronutrients increases the biological yield [23], this may be due to better crop nutrition through foliar application of the applied nutrients which may result in improved crop growth and [1] mention that more than one foliar spray of micronutrients mixture starting at tillering improve the biological yield. The same results were affirmed by another research achieved by [4,14,31].…”
Section: Weight Of Dray Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…) these nutrients improved the effectiveness and efficiency of each other and helped the plants to gain more weigh and produce more outcomes. Ali et al [28] advocated that biological yield was increased with spray of B. Khan et al [29] observed increase in biological yield with application of micronutrients.…”
Section: Biological Yield (Kg Ha -1 )mentioning
confidence: 99%
“…The results of this experiment illustrated that the application of Fe and Zn nutrition on wheat and its succeeding effects on rice significantly improved the grain, straw, and biological yield over the treatment that did not receive any Fe and Zn nutrition (Table 1). Fe is an important constituent of chlorophyll pigment, a component of different proteins and enzymes which help in chlorophyll synthesis, enhance the photosynthesis process [57,58], and lead to greater biomass production (Table 1). The application of treatment N 3 recorded the highest yield (grain, straw, and biological) of wheat and rice.…”
Section: Yieldmentioning
confidence: 99%